Estudo integrado do potencial fitorremediador da Eichhornia crassipes em ambientes naturais e sua utilização para obtenção de extratos proteicos - Martins, Daniel Freitas Freire (2014)
This study aimed to analyze the phytoremediation potential of Eichhornia crassipes in natural environments, optimize the extraction process of crude protein from plant tissue and, obtain and characterize this process in order to determine its viability of use instead of the protein sources of animal and/or human feed. For this, it has been determined in Apodi/Mossoró river water the concentration of ammonium ions, nitrite, nitrate, calcium, magnesium, potassium, iron, copper, manganese, zinc, nickel, cobalt, sodium, aluminum, cádmium, lead, and total chromium; It was determined in plant tissue of aquatic macrophytes of Eichhornia crassipes species present in Apodi/Mossoró River the moisture content, ash, calcium, magnesium, potassium, iron, copper, manganese, zinc, nickel, cobalt, sodium, aluminum, cadmium, lead, total chromium, total nitrogen and crude protein. It was also determined the translocation factor and bioaccumulation of all the quantified elements; It was developed and optimized the extraction procedure of crude protein based on the isoelectric method and a factorial design 24 with repetition; It was extracted and characterized the extract obtained by determining the moisture content, ash, magnesium, potassium, iron, copper, manganese, zinc, nickel, cobalt, sodium, cadmium, total nitrogen and crude protein. And finally, it was also characterized the protein extract using Thermogravimetric Analysis (TG), Derived Thermogravimetric (DTG), Differential Scanning Calorimetry (DSC), Infrared Spectroscopy (FT-IR) and jelly-like electrophoresis of polyacrylamide (SDS -PAGE) to assess the their molecular weights/mass. Thus, from the results obtained for the translocation and bioaccumulation factors was found that the same can be used as phytoremediation agent in natural environments of all quantified elements. It was also found that the developed method of extraction and protein precipitation was satisfactory for the purpose of the work, which gave the best conditions of extraction and precipitation of proteins as: pH extraction equal to 13.0, extraction temperature equals 60 ° C, reaction time equals to 30 minutes, and pH precipitation equals to 4.0. As for the extract obtained, the total nitrogen and crude protein were quantified higher than those found in the plant, increasing the crude protein content approximately 116.88% in relation to the quantified contente in the vegetal tissue of macrophyte. The levels of nickel and cadmium were the unique that were found below the detection limit of used the equipment. The electrophoretic analysis allowed us to observe that the protein extract obtained is composed of low polypeptide chains by the molecular and phytochelatins, with 6 and 15 kDa bands. Analysis of TG, DTG, DSC and FT-IR showed similarities in protein content of the obtained extracts based on different collection points and 9 parts of the plant under study, as well as commercial soy protein and casein. Finally, based on all these findings, it was concluded that the obtained extract in this work can be used instead of the protein sources of animal feed should, before that, test its digestibility. As human supplementation, it is necessary to conduct more tests associated with the optimization process in the sense of removing undesirable components and constant monitoring of the water body and the raw material used